"It's what makes us unique": Indigenous Australian perspectives on genetics research to improve comorbid mental and chronic disease outcomes. (3rd July 2022) - Nasir, Bushra Farah; Vinayagam, Ritwika; Rae, Kym
Abstract: Background: The role of personalized treatment approaches, including those based on genetic testing, are increasingly enabling informed decision-making to improve health outcomes. Research involving Indigenous Australians has been lagging behind, although this population experiences a higher prevalence of chronic disease and mental health disorders. Methods: Using community-based participatory research principles, this study purposefully interviewed participants with a diagnosed common mental disorder and a comorbid chronic disease condition. This was an inductive thematic analysis on semi-structured interviews with consenting participants ( n  = 48). Common themes and analytical domains were identified that provided a semantic understanding shared by participants. Results: Five emerging themes were identified, primarily focusing on: (1) The perceptions and understanding of genetics research; (2) culturally appropriate conduct of genetics research; (3) the role of indigenous-led genetics research; (4) future prospects of genetics research; and (5) the importance of genetics research for patients with mental and physical health comorbidities. Conclusion: Indigenous Australians are under-represented in pharmacogenomics research despite well-documented epidemiological research demonstrating that Indigenous people globally experience greater risk of developing certain chronic diseases and more severe disease progression. Positive outcomes from this study highlight the importance of not only involving Indigenous participants, but providing leadership and governance opportunities for future genetics research.